Analysis of Physical Education Learning Quality State Elementary Schools Producing O2SN Athletes 2025: Teachers' Perspectives - Marini Nurmalasari; Aam Ali Rahman; Tedi Supriyadi (Journal of Physical Education Health and Sport, 2026)
This study was motivated by the significant gap between primary schools in producing athletes for the National Student Sports Olympics (O2SN), which indicates variations in the quality of physical education instruction. This study aims to comprehensively analyse the quality of physical education learning in influencing the success of schools in developing O2SN athletes from the teachers' perspective. Using a qualitative design with a phenomenological approach, this study involved 15 physical education teachers from public primary schools in Rancakalong Subdistrict, selected through purposive sampling. Data were collected over two months through semi-structured interviews, questionnaires, and observations, with validity ensured through triangulation, and analysed using a thematic and descriptive approach. The results, visualised through a hierarchy chart, reveal that the most dominant factors in the success of producing athletes are contextual conditions (talent identification and differentiated learning) and teacher action strategies (varied methods, motivation, and individual guidance). Teachers play a crucial role as the primary filter in identifying student potential through regular learning integrated with additional training and extracurricular programmes. Although limited facilities are a major obstacle, teachers' creativity in modifying equipment maintains instructional effectiveness. This study concludes that O2SN achievements are a systemic accumulation of pedagogical quality, students' intrinsic interest, and school support that synergises intracurricular activities with athletic development.